Anticancer Effects of I-BET151, an Inhibitor of Bromodomain and Extra-Terminal Domain Proteins - Lai, Jiacheng; Liu, Ziqiang; Zhao, Yulei; Ma, Chengyuan; Huang, Haiyan (Frontiers in Oncology, 2021)
I-BET151 is an inhibitor of bromodomain and extra-terminal domain (BET) proteins that selectively inhibits BET family members (BRD2, BRD3, BRD4, and BRDT). Over the past ten years, many studies have demonstrated the potential of I-BET151 in cancer treatment. Specifically, I-BET151 causes cell cycle arrest and inhibits tumor cell proliferation in some hematological malignancies and solid tumors, such as breast cancer, glioma, melanoma, neuroblastoma, and ovarian cancer. The anticancer activity of I-BET151 is related to its effects on the pathways of NF-κB, Notch, and Hedgehog signal transduction, as well as on telomere elongation. Remarkably, the combination of I-BET151 with select anticancer drugs can partially alleviate the occurrence of drug resistance in chemotherapy. Especially, the combination of forskolin, ISX9, CHIR99021, I-BET151 and DAPT allows GBM cells to be reprogrammed into neurons, and this process does not experience an intermediate pluripotent state. The research on the anticancer mechanism of I-BET151 will lead to new treatment strategies for clinical cancer.